ANÁLISE DE DESEMPENHO DOCENTE EM CURSO DE ADMINISTRAÇÃO À DISTÂNCIA (ADMPG Journal, 2021)
The internal resources of an organization are fundamental to its performance in the market. The Resource-Based View (VBR) considers that an organization's resources are critical to achieving competitive advantage. As in Universitys professors have a prominent role, as they actively work in the teaching and learning process, and for this reason they are considered important resources for such organizations. Thus, the aim of this article is to develop a preliminary model that makes it possible to analyze the professors performance who work in the distance education (EaD). This qualitative research is used to collect data from interviews with course coordinators and professors from IES teaching in the distance education mode. From the operationalization of the model as preliminary results, it was identified that the model made it possible to outline teaching performances. Regarding the items that make up the model, it was observed that the 'pedagogical training' showed better results, with a performance level classified as above market. While the items: 'teaching practice' and 'academic qualification' presented performances at the market level. The research allowed participants to observe the professor performance profiles in the items that make up the model. Thus, the proposed preliminary model offers participants parameters in relation to the market in which they operate.